2012
DOI: 10.1002/open.201100003
|View full text |Cite
|
Sign up to set email alerts
|

High Cytotoxic Activity of Phosphonium Salts and Their Complementary Selectivity towards HeLa and K562 Cancer Cells: Identification of Tri‐n‐butyl‐n‐hexadecylphosphonium bromide as a Highly Potent Anti‐HeLa Phosphonium Salt

Abstract: Quaternary ammonium and phosphonium salts have been screened for their toxic effect on HeLa and K562 cancer cell lines, as well as on normal HUVEC cells. Tri-n-butyl-n-hexadecylphosphonium bromide, the first phosphonium salt with a halogen anion tested against HeLa cells, was 12 times more potent (IC50 <5 μm after 24 and 48 h) than the clinically used reference compound cisplatin and 17 times more potent than tri-n-hexyltetradecylphosphonium bis(trifluoromethylsulfonyl)imide, which, to the best of our knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Reference 2 did not show any toxicity in the dark, unlike 13 , which was not significantly toxic up to a concentration of 5 μ m and then showed enhanced toxicity with increasing concentration (data not shown). This is in keeping with the finding that phosphonium salts can display toxic activity toward cancer cell lines . When irradiated at 5 μ m , 2 did not show any toxicity, unlike 13 , which was markedly more toxic, in keeping with its accumulation into mitochondria (Figure ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Reference 2 did not show any toxicity in the dark, unlike 13 , which was not significantly toxic up to a concentration of 5 μ m and then showed enhanced toxicity with increasing concentration (data not shown). This is in keeping with the finding that phosphonium salts can display toxic activity toward cancer cell lines . When irradiated at 5 μ m , 2 did not show any toxicity, unlike 13 , which was markedly more toxic, in keeping with its accumulation into mitochondria (Figure ).…”
Section: Resultssupporting
confidence: 87%
“…This is in keeping with the finding that phosphonium salts can display toxic activity toward cancerc ell lines. [33] When irradiated at 5 mm, 2 did not show any toxicity, unlike 13,w hichw as markedlym ore toxic, in keepingw ith its accumulationi nto mitochondria ( Figure 5).…”
Section: Cytotoxicity Of Compounds 2a Nd 13 Against Human Lung Adenocmentioning
confidence: 88%
“…These cancer cell lines are commonly used as models to evaluate anticancer activities of new anticancer materials . We observed that the half‐maximal inhibitory concentration (IC 50 ) of 2 for HeLa cells was 25 µg mL −1 , which is comparable with the IC 50 of the commercial metallodrug cisplatin (16.5 µg mL −1 ). Red light irradiation enhanced the anticancer effect of 2 : the IC 50 value of 2 for HeLa cells after irradiation was as low as 2.5 µg mL −1 .…”
mentioning
confidence: 76%
“…Apart from few very ad hoc “system biology” studies, as the one just mentioned, there are several studies highlighting the specificity of ILs towards cancer cells and their ability to kill those cells, leaving healthy cells almost unaffected (Kumar and Malhotra 2009 ; Malhotra and Kumar 2010 ; Wang et al 2015 ; Stromyer et al 2020 ). In this context, it has been shown, for example, that tri- n -butyl- n -hexadecyl-phosphonium bromide—a phosphonium-based IL with a halogen anion and balanced lengths of C 4 and C 16 alkyl chains—is approximately 100 times more toxic against HeLa cells than several ammonium-based ILs, but it remains inactive against human chronic myelogenous leukemia K562 cells; complementarily, triphenyl-alkyl-phosphonium iodides, with shorter C 1 and C 5 alkyl chains, resulted to be inactive against HeLa cells, but very active against K562 cells (Bachowska et al 2012 ). More recently, (i) a novel betulinic acid–derived IL, i.e., [P 6,6,6,14 ][BA], has shown a specific cytotoxicity against human hepatocellular carcinoma HepG2 and human lung carcinoma A459 tumor cell lines (Silva et al 2019 ), and (ii) a new imidazolium IL with a triphenylphosphonium substituent, applied intravesically to mouse, has selectively killed bladder cancer cells, leaving adjacent healthy cells unaffected (Stromyer et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%